2014
DOI: 10.1161/jaha.114.001268
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Hypertension in a Population at Risk for Cardiovascular Disease: The Henry Ford ExercIse Testing (FIT) Project

Abstract: BackgroundIncreased physical fitness is protective against cardiovascular disease. We hypothesized that increased fitness would be inversely associated with hypertension.Methods and ResultsWe examined the association of fitness with prevalent and incident hypertension in 57 284 participants from The Henry Ford ExercIse Testing (FIT) Project (1991–2009). Fitness was measured during a clinician‐referred treadmill stress test. Incident hypertension was defined as a new diagnosis of hypertension on 3 separate cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 31 publications
3
50
0
5
Order By: Relevance
“…Comparable findings have been reported in ongoing follow-up studies from cohorts including the Veterans Exercise Testing Study, [17][18][19]22 the Aerobics Center Longitudinal Study (ACLS), 2,5,13,20,51 and the Henry Ford Exercise Testing Project. [52][53][54] Importantly, the overall discriminative ability of CRF in these studies is comparable to that normally obtained in widely used risk models, such as the Framingham risk score and European SCORE (Systematic Coronary Risk Evaluation) algorithm. 55,56 For example, Laukkanen et al 57 reported that a 1-MET increment in CRF and a 1% increment in European risk score were associated with 16% and 15% changes, respectively, in risk for all-cause mortality.…”
Section: Crf and Cvd Mortality In Asymptomatic Populationssupporting
confidence: 62%
“…Comparable findings have been reported in ongoing follow-up studies from cohorts including the Veterans Exercise Testing Study, [17][18][19]22 the Aerobics Center Longitudinal Study (ACLS), 2,5,13,20,51 and the Henry Ford Exercise Testing Project. [52][53][54] Importantly, the overall discriminative ability of CRF in these studies is comparable to that normally obtained in widely used risk models, such as the Framingham risk score and European SCORE (Systematic Coronary Risk Evaluation) algorithm. 55,56 For example, Laukkanen et al 57 reported that a 1-MET increment in CRF and a 1% increment in European risk score were associated with 16% and 15% changes, respectively, in risk for all-cause mortality.…”
Section: Crf and Cvd Mortality In Asymptomatic Populationssupporting
confidence: 62%
“…Si se analiza de manera separada los factores que formaron parte del patrón de conductas no saludables, en estudios previos se ha observado que el consumo de alcohol 17 y la baja actividad física 8,18 se asocian con aumento en la presión arterial. Con respecto al consumo de alcohol, se muestra que en los hombres éste puede ser mayor que en las mujeres 19 la administración aguda de nicotina a humanos o animales, aparentemente, tienen un efecto en las mediciones de norepinefrina (o noradrenalina), proponiéndose la hipótesis de que esta droga produce efectos psicológicos por la alteración del sistema de señalización noradrenérgico.…”
Section: Discussionunclassified
“…El consumo de drogas ilegales ha incrementado su prevalencia en un 114,3% del 2002 (0,7%) al 2011 (1,5%) 7 . Por otro lado, la actividad física es un factor que se ha asociado como protector, con relación a la presión arterial elevada, en donde individuos, adultos o adolescentes, con mayor actividad física tienen menor riesgo de trastornos en la presión arterial 8 . En México, el 42,2% de los escolares realiza menos de 4 horas de actividad física a la semana 9 .…”
Section: Introductionunclassified
“…[2,3] The level of PF was associated with degenerative diseases such as hypertension, metabolic syndrome, diabetes, and cognitive impairment. [4,5] The elderly aged population requires special attention with respect to health and social issues. The health of the elderly proceeds on a continuum that begins with development symptoms associated with daily activity changes, musculoskeletal degenerative, cognitive impairment, continues to disease onset, functional loss and disability, and ultimately, terminal status and death.…”
Section: National Journal Of Physiology Pharmacy and Pharmacologymentioning
confidence: 99%